Study of A Novel Environmentally Responsive Ophthalmic Drug Delivery System - PRASHANT K. DESHMUKH; RAVINDRA A. FURSULE (International Journal of Pharma and Bio Sciences, 2010)
Targeting the drug to the appropriate site of action is usually one of the greatest challenges in drug delivery to the eye because of its anatomical and physiological nature. Pre-application an environmentally responsive systems are in the liquid state and easily administered in to eye whereas post-application, they are transformed in highly viscous gel. In present study temperature triggered and ion activated environmentally responsive system was prepared for ocular drug delivery by using poloxamer-407 and sodium alginate. All prepared formulations were transparent and clear and the gel formed in vitro produced sustained drug release up to eight hours. Rheological behaviors of all formulations were not affected by addition of model drug. Antimicrobial activity of drug was not changed significantly due to formulation ingredients and conditions as compared to reference formulation (Marketed formulation). As the concept involved is novel and the methodology used for the preparation is simple as that of conventional ophthalmic liquid dosage form, it is industrially oriented and economical.